Disrupting activities in quality improvement initiatives: a qualitative case study of the QuICR Door-To-Needle initiative. Issue 12 (30th May 2019) - Huq, Jo-Louise; Woiceshyn, Jaana
Abstract : Background: Healthcare quality improvement (QI) efforts are ongoing but often create modest improvement. While knowledge about factors, tools and processes that encourage QI is growing, research has not attended to the need to disrupt established ways of working to facilitate QI efforts. Objective: To examine how a QI initiative can disrupt professionals' established way of working through a study of the Alberta Stroke Quality Improvement and Clinical Research (QuICR) Door-to-Needle Initiative. Design: A multisite, qualitative case study, with data collected through semistructured interviews and focus groups. Inductive data analysis allowed findings to emerge from the data and supported the generation of new insights. Findings: In stroke centres where improvements were realised, professionals' established understanding of the clinical problem and their belief in the adequacy of existing treatment approaches shifted—they no longer believed that their established understanding and treating the clinical problem were appropriate. This shift occurred as participants engaged in specific activities to improve quality. We identify these activities as ones that create urgency, draw professionals away from regular work and encourage questioning about established processes. These activities constituted disrupting action in which both clinical and non-clinical persons were engaged. Conclusions: Disrupting action is an important yet understudied element of QI. Disrupting action can be used to create gaps in established ways of working and may help encourage professionals' involvement and support of QI efforts. While non-clinical professionals can be involved in disrupting action, it needs to engage clinical professionals on their own terms.